2012
DOI: 10.3892/ol.2012.981
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of extracellular matrix metalloproteinase inducer, EMMPRIN/CD147, in human osteosarcoma

Abstract: Abstract. Osteosarcoma is the most common primary malignant bone tumor in children and adolescents. Recent studies have shown that extracellular matrix metalloproteinase inducer (EMMPRIN/CD147) promotes adhesion, invasion and metastasis of malignant tumor cells. The aim of this study was to investigate the impact of EMMPRIN/CD147 expression on prognosis and its correlation with clinicopathological characteristics in patients with osteosarcoma. The expression of EMMPRIN/CD147 in 55 surgical specimens from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…Enhanced EMMPRIN expression has been described before in many types of tumor tissues, but was usually not accompanied by detection of EMMPRIN expression on stromal cells (Zhong et al, 2008; Liang et al, 2009; Omi et al, 2012; Pinheiro et al, 2012; Lu et al, 2013), suggesting that stromal cell expression of EMMPRIN in vivo was very low and below the levels of antibody detection. Studies in vitro demonstrated that tumor cells enhance their expression of EMMPRIN when co-cultured with other cell types, such as fibroblasts (Tang et al, 2004; Sato et al, 2009) or endothelial cells (Caudroy et al, 2002; Bougaten et al, 2009), but expression of EMMPRIN in monocytes/macrophages co-cultured with tumor cells was hardly investigated.…”
Section: Discussionmentioning
confidence: 89%
“…Enhanced EMMPRIN expression has been described before in many types of tumor tissues, but was usually not accompanied by detection of EMMPRIN expression on stromal cells (Zhong et al, 2008; Liang et al, 2009; Omi et al, 2012; Pinheiro et al, 2012; Lu et al, 2013), suggesting that stromal cell expression of EMMPRIN in vivo was very low and below the levels of antibody detection. Studies in vitro demonstrated that tumor cells enhance their expression of EMMPRIN when co-cultured with other cell types, such as fibroblasts (Tang et al, 2004; Sato et al, 2009) or endothelial cells (Caudroy et al, 2002; Bougaten et al, 2009), but expression of EMMPRIN in monocytes/macrophages co-cultured with tumor cells was hardly investigated.…”
Section: Discussionmentioning
confidence: 89%
“…The role of EMMPRIN, also known as CD147, in the process of tumor development, invasion and metastasis is a popular topic in the field of the cellular biology of tumors ( 11 ). The proliferative activity of tumor cells is closely associated with tumor invasion ( 12 ), metastasis ( 13 ) and prognosis ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not employ any three-dimensional culture systems to examine the effects of microenvironmental factors on spheroidal tumor cell aggregates, which recapitulate in vivo tumor growth more closely; such three-dimensional cellular growth influences cell metabolism and, combined with hypoxia, can increase invasive potential in MG63 cells (41, 42). Finally, as with any in vitro system for the study of malignant tumors, the lack of an extracellular matrix (ECM) precludes the examination of any factors which could contribute further additive effects to tumor cell growth and metastatic potential; in the case of OS, the influences of MMP/TIMP interactions and ECM-associated growth factors on invasive potential have been examined but have not yet been fully elucidated (14, 15, 4347). However, despite these limitations, this study suggests that tumor microenvironmental factors must be considered in aggregate and that the control of tumor microenvironmental factors, and/or expression of CA IX and VEGF, should be among the important targets for examination in the development of future therapies for malignant tumors.…”
Section: Discussionmentioning
confidence: 99%